Vacuum packaged embalmed dogs for veterinary surgery practicing - Del Ponti, Isabela [UNESP]; Vieira, Giovana C. [UNESP]; Soares, Laura G. [UNESP]; Rodrigues, Alessandra [UNESP]; Costa, Natalia T. B. [UNESP]; Ferreira, Geovana C. [UNESP]; Fechis, Alisson D. S. [UNESP]; Queiroz, Andrea B. P. S. [UNESP]; Oliveira, Fabricio S. [UNESP] (Soc Anatomica Espanola, 2021)
It is imperative to have a lot of discretion regarding animals' use in research and teaching activities. Consequently, the search for alternative methods that do not cause academic or scientific damage is essential. This research aims to determine the maximum rupture force and the rupture elongation of the skin and the students' evaluation of the embalmed dogs' cadaver for veterinary surgery classes. Cadavers were injected with 120 mL/kg of a 20% sodium chloride, 1% nitrite and 1% sodium nitrate solution, and 150 mL/kg of alcohol with 5% glycerin and kept in vacuum packages between 0 to 4 degrees C. Eight dogs constituted group 1, and three skin samples were collected on day 0 (fresh samples/before fixation) and during the next seven consecutive days. Only days 2 and 6 were different from the control. Group 2 was analyzed by 46 undergraduate students during the veterinary surgery classes, who completed a form about malleability and incision/suture of the tissue. Using a scale from zero to ten, the reached value was 7.95, and 100% of the students approved the use of embalmed dogs for surgical training. The anatomical technique had an excellent cost-benefit ratio in addition to reduced environmental impact. The method maintained malleability and quality of incision and suture in surgical practice.
Keywords: Anatomy; Conservation; Learning; Malleability; Teaching